2020
DOI: 10.1002/elsc.202000054
|View full text |Cite
|
Sign up to set email alerts
|

Online monitoring applying the anaerobic respiratory monitoring system reveals iron(II) limitation in YTF medium for Clostridium ljungdahlii

Abstract: Online monitoring of microbial cultures is an effective approach for studying both aerobic and anaerobic microorganisms. Especially in small‐scale cultivations, several parallel online monitored experiments can generate a detailed understanding of the cultivation, compared to a situation where a few data points are generated from time course sampling and offline analysis. However, the availability of small‐scale online monitoring devices for acetogenic organisms is limited. In this study, the previously report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Different studies investigated trace element composition and showed the inherent potential in fermentation optimization by adjusting the trace element composition 31,42,43 . YTF medium is a medium commonly employed for heterotrophic growth of C. ljungdahlii 36,45–49 . Since YTF (Yeast extract‐Tryptone‐Fructose) medium only contains the trace elements provided through yeast extract and tryptone, it is debatable whether all required trace elements for the maximum activity of the WLP are provided in this medium.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Different studies investigated trace element composition and showed the inherent potential in fermentation optimization by adjusting the trace element composition 31,42,43 . YTF medium is a medium commonly employed for heterotrophic growth of C. ljungdahlii 36,45–49 . Since YTF (Yeast extract‐Tryptone‐Fructose) medium only contains the trace elements provided through yeast extract and tryptone, it is debatable whether all required trace elements for the maximum activity of the WLP are provided in this medium.…”
Section: Introductionmentioning
confidence: 99%
“…To study the impact of trace metals on metabolic activity, the anaerobic Respiration Activity Monitoring System (anaRAMOS) device was used. The anaRAMOS offers the possibility of real‐time online monitoring of the carbon dioxide transfer rate (CTR) in up to eight parallel shake flasks 49,50 . The measured CTR is a direct quantitative indication of metabolic activity and can be used to calculate the total amount of produced net CO 2 (CT).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In anaerobic applications, CTR and the total gas transfer rate (TGTR) were used to identify diauxic growth, and to predict the hydrogen production by Clostridium pasteurianum (Munch et al, 2019). The anaRAMOS was also described as a potent tool for online monitoring of the cultivation of acetogenic Clostridia on dissolved solid substrates, such as fructose (Mann et al, 2020). Cultivation using a continuous supply of gaseous carbon and energy substrates has not been possible so far.…”
Section: Introductionmentioning
confidence: 99%